2021
DOI: 10.1002/acn3.51285
|View full text |Cite
|
Sign up to set email alerts
|

Association between infectious burden and cerebral microbleeds: a pilot cross‐sectional study

Abstract: Objective Cerebral microbleeds (CMBs) is a subtype of cerebral small vessel disease. Their underlying pathogenesis remains unclear. The aim of this study was to investigate the association between infectious burden (IB) and CMBs. Methods Seven hundred and seventy‐three consecutive patients who were hospitalized in the Department of Neurology in General Hospital of Western Theater Command without severe neurological symptoms were recruited and selected in this pilot cross‐sectional study. CMBs were assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Additional limitations of this instrument include the level of knowledge needed to identify several infectious diseases increasing the possibility of underreport [ 31 ]. Hence, the literature favors alternative approaches to measure infection burden such as antibody titers and disability adjusted life years (DALY) [ 21 52 53 54 55 ]. Nevertheless, self-report questionnaires are considered reliable and valid and are frequently used in epidemiological studies to complement objective data [ 48 56 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional limitations of this instrument include the level of knowledge needed to identify several infectious diseases increasing the possibility of underreport [ 31 ]. Hence, the literature favors alternative approaches to measure infection burden such as antibody titers and disability adjusted life years (DALY) [ 21 52 53 54 55 ]. Nevertheless, self-report questionnaires are considered reliable and valid and are frequently used in epidemiological studies to complement objective data [ 48 56 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation exerts the role as an essential part of CMBs pathogenesis and one of CMBs’ most significant risk factors. A pilot cross-sectional study showed an association between the presence of CMBs and infection with multiple pathogens, such as herpes simplex virus (HSV)-1 and HSV-2 [ 178 ]. Histopathological evidence demonstrated that hemosiderin deposits at the lesion site of CMBs are often surrounded by macrophages, a type of immune cells that further initiate inflammatory responses.…”
Section: The Prevalence and Factors Influencing The Clinical Presentation Of Cerebral Microbleedsmentioning
confidence: 99%
“…However, other pathologies (traumatic brain injuries, chronic kidney disease, and chronic infections) may account for their occurrence. 35 In addition, CMB have been reported after radiation therapy, certain endovascular procedures and with the use of some medications. 68…”
Section: Introductionmentioning
confidence: 99%
“…However, other pathologies (traumatic brain injuries, chronic kidney disease, and chronic infections) may account for their occurrence. [3][4][5] In addition, CMB have been reported after radiation therapy, certain endovascular procedures and with the use of some medications. [6][7][8] Several cross-sectional studies have addressed CMB prevalence, which varies from 3% to >30% according to age and other characteristics of the study population.…”
Section: Introductionmentioning
confidence: 99%